Effect of photodynamic therapy on clinical isolates of Staphylococcus spp - Miyabe, Michelle [UNESP]; Junqueira, Juliana Campos [UNESP]; Costa, Anna Carolina Borges Pereira da [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Ribeiro, Martha Simões; Feist, Ilíria Salomão (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
Staphylococcus spp. are opportunistic microorganisms known for their capacity to develop resistance against antimicrobial agents. The objective of this study was to evaluate the effect of photodynamic therapy (PDT) on 20 Staphylococcus strains isolated from the human oral cavity, including S. aureus, S. schleiferi, S. epidermidis, S. capitis, S. haemolyticus, and S. lentus. A suspension of each Staphylococcus strain (10(6) cells/mL) was submitted to PDT using methylene blue and a low power laser. The isolated effects of methylene blue, laser treatment and ciprofloxacin were also evaluated. After the experimental treatments, 0.1 mL aliquots of the suspensions were seeded onto BHI agar for determination of the number of colony-forming units (CFU/mL). The results were analyzed by analysis of variance and Tukey's test (p < 0.05). The mean reduction in bacterial counts of the strains submitted to PDT ranged from 4.89 to 6.83 CFU (log10)/mL, with the observation of a decreasing susceptibility to treatment of S. schleiferi, S. haemolyticus, S. epidermidis, S. capitis, S. aureus, and S. lentus. The results showed that PDT was effective in reducing the number of viable cells of all clinical Staphylococcus isolates studied.
Keywords: Staphylococcus; Photochemotherapy; Methylene Blue; Ciprofloxacin